2012
DOI: 10.1051/0004-6361/201218929
|View full text |Cite
|
Sign up to set email alerts
|

The ionized and hot gas in M17 SW

Abstract: Aims. With new THz maps that cover an area of ∼3.3 × 2.1 pc 2 we probe the spatial distribution and association of the ionized, neutral and molecular gas components in the M17 SW nebula. Methods. We used the dual band receiver GREAT on board the SOFIA airborne telescope to obtain a 5. 7 × 3. 7 map of the 12 CO J = 13-12 transition and the [C II] 158 μm fine-structure line in M17 SW and compare the spectroscopically resolved maps with corresponding ground-based data for low-and mid-J CO and [C I] emission. Resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…4.3.3, refer to a gas density of >10 5 cm −3 if they are compared to PDR models (Burton et al 1990). The high-density nature of M 17 SW is also evidenced by the molecular gas persisting just west of the IF (Pérez-Beaupuits et al 2012). This can be interpreted as the result of self-shielding of molecules in high-density PDR, which can move the transition regions for H i/H 2 close to the surface of the cloud (Burton et al 1990).…”
Section: Properties Of M 17 Swmentioning
confidence: 91%
“…4.3.3, refer to a gas density of >10 5 cm −3 if they are compared to PDR models (Burton et al 1990). The high-density nature of M 17 SW is also evidenced by the molecular gas persisting just west of the IF (Pérez-Beaupuits et al 2012). This can be interpreted as the result of self-shielding of molecules in high-density PDR, which can move the transition regions for H i/H 2 close to the surface of the cloud (Burton et al 1990).…”
Section: Properties Of M 17 Swmentioning
confidence: 91%
“…However, velocity resolved mapping observations of the [C ii] emission in Galactic regions have recently been made with the Heterodyne Instrument for the Far-Infrared (HIFI) on Herschel and are being made with the German REceiver for Astronomy at Terahertz Frequencies (GREAT) on board the Stratospheric Observatory for Infrared Astronomy (SOFIA), and they show complex line profiles of the [C ii] emission, typically substantially wider than expected from the [C i] and low-or mid-J CO emission profiles. The velocity information is thus essential in order to identify the origin of the [C ii] emission (Pérez-Beaupuits et al 2012;Carlhoff 2013), and the significant difference in the velocity profile of the [C ii] emission from the low-or mid-J CO emission indicates that a substantial fraction of the [C ii] emission is accelerated relative to the quiescent material, e.g., it undergoes ablation or is blown off (Dedes et al 2010;Mookerjea et al 2012;Okada et al 2012;Schneider et al 2012;Simon et al 2012;Pilleri et al 2012). These results emphasize the need of velocity resolved observations to distinguish different velocity components with their different physical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent SOFIA/GREAT observations of the velocityresolved [C II] spectra showed that a large fraction (>60%) of the [C II] emission, observed at the lower (<10 km s −1 ) and higher (>24 km s −1 ) velocity channels, is not associated with the starforming material (denser and colder gas) traced by species like CO and [C I], which has an average line width of 5 to 10 km s −1 centered at V LSR = 20 km s −1 (Pérez-Beaupuits et al 2012, 2013. Only the central narrow (1 km s −1 ) channel maps of the velocity-resolved [C II] spectra show a spatial association with other gas tracers (e.g., [C I] and 12 CO).…”
Section: Introductionmentioning
confidence: 99%